2017
DOI: 10.1103/physreva.95.013833
|View full text |Cite
|
Sign up to set email alerts
|

Mode Q factor and lasing spectrum controls for deformed square resonator microlasers with circular sides

Abstract: Deformed square resonators with the flat sides replaced by circular sides are proposed and demonstrated to enhance mode Q factors and adjust transverse mode intervals using the regular ray dynamic analysis and numerical simulations. Dual-transverse-mode emissions due to the ultrahigh-Q factors with different wavelength intervals are realized experimentally for AlGaInAs/InP circular-side square microlasers, and the stationary condition of the dual-mode emission is satisfied because the high-Q confined modes hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The p and q are different for the near high-Q WGMs, and therefore stable dual-mode lasing can be expected for the square microcavity laser. In the deformed square microcavity with circular-sides [56] or variable curvature, [57] the overlap of mode field intensities between even the near high-Q WGMs is less than that of the non-deformed square microcavities according to the numerical simulations. Thus, stable dual-mode lasing can also be achieved for the deformed square microcavity laser with an enhanced wavelength interval.…”
Section: Tunable Wavelength Intervals In Dual-transversemode Square M...mentioning
confidence: 88%
See 3 more Smart Citations
“…The p and q are different for the near high-Q WGMs, and therefore stable dual-mode lasing can be expected for the square microcavity laser. In the deformed square microcavity with circular-sides [56] or variable curvature, [57] the overlap of mode field intensities between even the near high-Q WGMs is less than that of the non-deformed square microcavities according to the numerical simulations. Thus, stable dual-mode lasing can also be achieved for the deformed square microcavity laser with an enhanced wavelength interval.…”
Section: Tunable Wavelength Intervals In Dual-transversemode Square M...mentioning
confidence: 88%
“…In order to further enhance the wavelength interval of the dual-transverse-mode square microcavity laser, we proposed and demonstrated deformed square microcavities with their flat sides replaced by circular sides. [56] Figure 4(a) shows a schematic diagram of a deformed square microcavity laser with the flat sides replaced by circular sides, where a is the side length of the square, δ is the deformation parameter, and r is the radius of the circular side. Considering the mode field distributions of the fundamental and first-order transverse modes as shown in Figs.…”
Section: Tunable Wavelength Intervals In Dual-transversemode Square M...mentioning
confidence: 99%
See 2 more Smart Citations
“…By modifying the hexagon to a circular-side hexagonal resonator (CSHR), the Q factors of different transverse modes can be approximated, and then the multi-transverse modes can be realized. Recently, we realized dual-mode lasing with an adjusting interval in a square microcavity laser (Long et al, 2015) and demonstrated the enhancements of mode Q-factors and intervals in circular-side square microcavities (Weng et al, 2017). Circular sides were also applied to a hexagonal microcavity for enhancing mode Q factors and adjusting mode intervals (Xiao et al, 2017;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%